Asthma Symptoms in Bakeries at Parakou, Benin - Ade, Serge; Adjobimey, Mênonli; Agodokpessi, Gildas; Kouassi, Marie Sylvie; Gounongbe, Fabien A.; Cisse, Ibrahim; Hounkpatin, Spero H. R. (Pulmonary Medicine, 2020)
Background and Objectives. There is a dearth of information on asthma among bakers in low-income settings. The objectives of this study were to determine (i) the prevalence of asthma symptoms, (ii) factors associated with probable occupational asthma (OA), and (iii) work habits that might lead to a dusty workplace environment, Parakou, Benin. Materials and Methods. This was a mixed methods (cross-sectional quantitative and qualitative) study carried out between March and September 2018. Results. Of 210 employees/apprentices in 26 bakeries, 190 (91.48%) were included in the study: median age was 25.50 (IQR=22−32) years, 157 (82.63%) were aged <40 years, and the male-to-female ratio was 26.14. Of these, 111 (58.42%) worked in a salted bread and 79 (41.58%) in a sweet bread bakery. An asthma history was reported by 3.68%. Symptoms consistent with asthma, work-related asthma, OA, and work-aggravated asthma were found in 13.68%, 12.63%, 10%, and 2.63%, respectively. Asthma confirmation was obtained in 15.79% of bakers with probable OA and in 23.08% of all bakers with suspected asthma. A history of allergic rhinoconjunctivitis was associated with probable OA (aOR=106; 95%CI=17.79−2093; p<0.001). Of the 24 bakers with probable work-related asthma, 3 (12.50%) were prescribed a short-acting beta2-agonist and 2 (8.33%) an inhaled corticosteroid. No worker had had a systematically planned annual medical visit; some habits at work were identified as leading to flour and dust suspension at the workplace. Conclusion. Clinical manifestations of OA were common among bakers in Parakou and were associated with allergic rhinoconjunctivitis. There is a need to improve technical preventive measures and treatment, as well as to institute systematic medical visits for these workers.